Low-temperature sintered Bi1-xSmxNbO4 microwave dielectrics - Lim, Hyuk; Oh, Young-Jei (ELSEVIER SCI LTD, 2020)
The Bi1-xSmxNbO4 ceramics (x = 0 similar to 0.1) was prepared by a conventional solid-state reaction at a low temperature from 900 degrees C to 960 degrees C. The crystal structures of the Bi1-xSmxNbO4 ceramics were single orthorhombic (alpha-BiNbO4) phase at all sintering conditions. Dielectric constant (epsilon(r)), Quality factor (Q.f), and the Temperature coefficient of resonant frequency (tau(r)) were significantly affected by Sm3+ substitution. The epsilon(r) ranged from 42.79 +/- 0.5 to 41.71 +/- 0.5, with the highest Qf value of 32,100 +/- 1605 GHz in the Bi1-0.99Sm0.01NbO4 ceramic. The Q.f values of the Bi1-xSmxNbO4 ceramics were improved compared to the BiNbO4 ceramics. The tau(f) of the Bi1-xSmxNbO4 ranged from -2.3 +/- 0.5 ppm/degrees C to -11.4 +/- 0.5 ppm/degrees C. The Clausius-Mossotti equation and additivity rule of dielectric polarizabilities were introduced in order to explain dependence of the dielectric constant as a function of Sm content. The tau(f) of the Bi1-xSmxNbO4 ceramics with Sm content also was associated with the bond valence of the Bi1-xSmxNbO4 ceramics.
Keywords: BINBO4 CERAMICS; IONS; V2O5